FAKTOR-FAKTOR YANG MEMENGARUHI NILAI PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI - Himawan, Joenardi; Susanto, Liana (Fakultas Ekonomi, Universitas Tarumanagara, 2024)
This study aims to determine whether there is an influence of profitability, liquidity, firm size, and managerial ownership factors on firm value in manufacturing companies listed on the Indonesia Stock Exchange in the period 2017 – 2019. The sample was selected by purposive sampling method and there were 39 companies that met the criteria. The data processing technique uses multiple regression analysis assisted by Eviews 11 SV software and Microsoft Excel 2016. The results of this study indicate that profitability has a significant positive effect on firm value, while liquidity, firm size and managerial ownership have no significant effect on firm value. The implication of this research is the need to increase company profitability to increase company value in order to attract more investors.